Antireflux mucosal intervention (ARMI) procedures for refractory gastroesophageal reflux disease: a systematic review and meta-analysis. (April 2022) - Yeh, Jen-Hao; Lee, Ching-Tai; Hsu, Min-Hung; Lin, Chi-Wen; Hsiao, Po-Jen; Chen, Chien-Lin; Wang, Wen-Lun
Background: Endoscopic treatments are increasingly being offered for refractory gastroesophageal reflux disease (GERD). Three procedures have similar concepts and techniques: antireflux mucosectomy (ARMS), antireflux mucosal ablation (ARMA), and antireflux band ligation (ARBL); we have collectively termed them antireflux mucosal intervention (ARMI). Here, we systematically reviewed the clinical outcomes and technical aspects. Methods: The PubMed, Embase, and Cochrane Library databases were searched from inception to October 2021. The primary outcome was the clinical success rate. The secondary outcomes were acid exposure time, DeMeester score, need for proton pump inhibitors (PPIs), endoscopic findings, and adverse events. Results: Fifteen studies were included. The pooled clinical success rate was 73.8% (95% confidence interval (CI) = 69%–78%) overall, 68.6% (95% CI = 62.2%–74.4%) with ARMS, 86.7% (95% CI = 78.7%–91.9%) with ARMA, and 76.5% (95% CI = 65%–85.1%) with ARBL. ARMI resulted in significantly improved acid exposure time, DeMeester score, and degree of hiatal hernia. Furthermore, 10% of patients had dysphagia requiring endoscopic dilatation after ARMS or ARMA, and ARMS was associated with a 2.2% perforation rate. By contrast, no bleeding, perforation, or severe dysphagia was noted with ARBL. Severe hiatal hernia (Hill grade III) may predict treatment failure with ARMA. Conclusions: The three ARMI procedures were efficacious and safe for PPI-refractory GERD. ARMA and ARBL may be preferred over ARMS because of fewer adverse events and similar efficacy. Further studies are necessary to determine the optimal technique and patient selection.